Economic determinants of international labour migration in EU/EFTA region 1985-1999 - Roel P.W. Jennissen (European Regional Science Association (ERSA), 2002)
This paper has been written within the framework of the research program 'Towards a dynamic scenario model for socio-economic determinants of population dynamics in Europe'. Within this research program, one PhD project is concerned with international migration. International migration hypotheses often lack a sound theoretical background. In the PhD project 'Economic Determinants of International Migration in Europe', an attempt is made to improve this theoretical background by quantifying the relationship between international migration and economic indicators. The aim of this paper is to estimate the influence of economic determinants on the most important international migration types in Europe in the period 1985-2000. Quantifying the influence of economic determinants on the most important international migration types in this period may contribute to the discussion about the demographic consequences of future economic development in Europe and extension of the European Union. Migrant flows, for which sufficient data are available will be used. The economic determinants that are estimated are GDP per capita, and unemployment. Furthermore, the effect of the migrant stock is taken into account as well. Pooled cross-sectional time series analysis will be used in separate models for each migration type.
Keywords: 330